Diterpenes, ionol-derived, and flavone glycosides from Podocarpus elongatus - Faiella, Laura; Temraz, Abeer; De Tommasi, Nunziatina; Braca, Alessandra (Phytochemistry (Oxford), 2012)
Six diterpenes, one ionol-derived and one flavone C-glycoside were isolated from the leaves of Podocarpus elongatus. Structures were elucidated by 1D and 2D NMR spectroscopy as well as by ESI mass spectrometry and chemical methods. [Display omitted] ► Nor- and bis-norditerpenes are interesting cytotoxic metabolites of Podocarpus genus. ► They are considered chemotaxonomic markers for the genus. ► It was performed a phytochemical study of Podocarpus elongatus leaves. ► Eight compounds were characterized including six diterpenes. Eight compounds, nagilactone C 7-O-α-l-arabinopyranosyl-(1→4)-β-d-xylopyranoside, nagilactone C 7-O-β-d-glucopyranosyl-(1→4)-β-d-xylopyranoside, nagilactone C 7-O-β-d-xylopyranoside, nagilactone A 7-O-α-l-arabinopyranosyl-(1→4)-β-d-xylopyranoside, 2β,15S,16,17,19-pentahydroxy-isopimar-8(14)-ene 17-O-β-d-glucopyranoside, 2β,15R,16,17,19-pentahydroxy-isopimar-8(14)-ene 17-O-β-d-glucopyranoside, 1-(2,6,6-trimethyl-4-hydroxycyclohexenyl)-1-hydroxy-buta-1-en-3-one 4-O-β-d-glucopyranoside, and vitexin 2″-O-β-d-(6‴-acetyl)-glucopyranoside together with 13 known compounds, were isolated from the leaves of Podocarpus elongatus. Structures were elucidated by 1D and 2D NMR spectroscopy as well as by ESI mass spectrometry and chemical methods. The absolute configurations of the 15,16-diol moieties in two compounds were determined using Snatzke’s method.